ACCOUNTABILITY OF USING BALANCED SCORECARD : PERFORMANCE MEASUREMENT MODEL OF SIDOARJO REGIONAL GENERAL HOSPITAL 2020-2022 - Nufaisa; Islami, Diany Natasya Fara (Universitas Nahdlatul Ulama Surabaya, 2024)
Sidoarjo Regional General Hospital (RSUD) is a Regional Public Service Agency. RSUD Sidoarjo has a responsibility towards public accountability for its performance, especially in terms of financial and service performance. The method used as a performance measurement tool is the balanced scorecard. This study aims to examine the effect of accountability on each of the balanced scorecard perspectives (financial, customer, internal business processes, learning and growth) to measure the performance of Sidoarjo Hospital for the period 2020 – 2022. The results in this study indicate that accountability has a positive effect on financial perspectives, customer perspectives, internal business process perspectives, learning and growth perspectives.This research provides input for the management of Sidoarjo Hospital in order to maximize the resources they have so that they can increase hospital revenue and make budget efficiencies, and carry out socialization of the innovations created.